2010
DOI: 10.1136/bjo.2009.175216
|View full text |Cite
|
Sign up to set email alerts
|

Short-term intraocular tamponade with perfluorocarbon heavy liquid

Abstract: Short-term perfluoro-n-octane tamponade achieved a stable reattachment rate of 76% when used to manage challenging retinal pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
35
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 25 publications
2
35
1
1
Order By: Relevance
“…15,28 We observed a high rate (32%) of a characteristic inflammation compared with some previous clinical studies using postoperative PFO for RD. [22][23][24] This may be because of the longer average duration of PFO used in the present study, or underrecognition and retrospective design of previous studies. Rush et al 22 have recently observed inflammation with posterior lens capsule deposits in a comparable proportion (8/39) of eyes with postoperative PFO and reported similar resolution after PFO removal and clinical management with topical corticosteroids.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…15,28 We observed a high rate (32%) of a characteristic inflammation compared with some previous clinical studies using postoperative PFO for RD. [22][23][24] This may be because of the longer average duration of PFO used in the present study, or underrecognition and retrospective design of previous studies. Rush et al 22 have recently observed inflammation with posterior lens capsule deposits in a comparable proportion (8/39) of eyes with postoperative PFO and reported similar resolution after PFO removal and clinical management with topical corticosteroids.…”
Section: Discussionmentioning
confidence: 72%
“…Intraocular pressure elevation is a well-described phenomenon in the context of silicone oil, 30 but it has been ill-defined regarding PFO as a vitreous substitute. Some previous retrospective series [22][23][24]26 involving a similar technique have reported no or lower incidence. Rush et al 22 recently reported IOP elevation in 36% of eyes treated with postoperative PFO that was associated with macroscopically detectable PFO in the anterior chamber, identical to our report.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations